Knowledge, attitude and preventive practices of COVID-19 among deaf persons in the Greater Accra region of Ghana - Reginald Arthur-Mensah Jnr; Jacob Nartey Quao; Louisa Yeboah; Zanu Dassah; Abigail Agartha Kyei (BMC, 2023)
Abstract Background Since the emergence of the COVID-19 pandemic, studies continue to investigate the KAP of COVID-19 among diverse groups. We examined the KAP of COVID-19 among deaf persons living in the Ayawaso North Municipality in Accra. Methods A descriptive cross-sectional design was used for this study. Our sample comprised deaf persons registered with the Municipal Directorate. In all, 144 deaf persons were interviewed using an adapted KAP COVID-19 questionnaire. Results Regarding knowledge, majority of the deaf persons (> 50%) were not in the know of 8 out of 12 items of the knowledge subscale. For attitude, deaf persons (> 50%) showed optimistic attitude in all 6 items of the attitude subscale. Deaf persons "always" practised 5 items and "sometimes" practised 4 items in the preventive practices to COVID-19. A positive moderate and significant correlation existed between the subscales. Regression analysis showed that, a one-unit increase in knowledge will result in a 1.033-unit increase in preventive practices while a one-unit increase in knowledge will result in a 0.587-unit increase in attitude. Conclusions Campaigns about COVID-19 should emphasize the teaching of the science of the virus and the disease and not just the preventive practices, paying special attention to deaf persons.